Kajian Historis Terhadap Janji Tuhan dalam Kitab Yesaya 42:18-43:21 serta Implikasi Teologisnya. - Sembiring, Theofilus; Simanungkalit, Hulman; Sihombing, Roma (STT Injili Indonesia Medan, 2022)
The purpose of this study is to clarify the concept of the promise that God gave to humans and specifically in the book of Isaiah 42:18-43:21. Because by explaining God's promises it will be easy to understand and easy to understand and clear to whom the promises were delivered and to whom the promises were given. Here the author will use the descriptive method, meaning that the data are collected as true facts from correct and reliable literary sources in order to contribute to the historical study of the text of Isaiah 42: 18 - 43: 21 to get accurate results. And the conclusion that the author makes is that God offers love to humans but there will be punishment too if humans violate the rules and laws that are determined by God. And God also wants to promise humans unconditionally and with conditions but every action has consequences. Blessings if you are obedient and faithful, curses or punishments if you turn loyal and disobedient.Â Keywords: Promise of God, Isaiah, concept